2023
DOI: 10.1080/21645515.2023.2176066
|View full text |Cite
|
Sign up to set email alerts
|

Side effects following first dose of COVID-19 vaccination in Ho Chi Minh City, Vietnam

Abstract: Vaccines are strongly recommended globally as an effective measure to prevent serious illness from and spread of COVID-19. Concerns about safety following vaccination continue to be the most common reason that people do not accept the vaccine. This retrospective study was carried out on 4341 people who received the first dose of ChAdOx1 nCoV-19, BBIBP-CorV, or mRNA-1273 vaccine at Jio Health Clinic in Ho Chi Minh City, Vietnam. Post-injection side effects were either reported by participants or actively collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Although no parameters were associated with the magnitude of the side effects after the first dose of the BNT162b2 and ChAdOx1-S vaccines, being female, having chronic diseases, taking medicines routinely, and having a history of SARS-CoV-2 infection were associated with the magnitude of side effects after the second dose of the BNT162b2 vaccine, and having a history of allergy and being female were associated with the magnitude of side effects after the second dose of the ChAdOx1-S vaccine. Previous studies have reported the presence of associations between: 1. having a history of allergies and having an allergic reaction to the vaccine [ 26 ], local side effects [ 27 ], and non-allergic side effects [ 26 ]; 2. female sex and a higher magnitude of side effects [ 16 , 28 , 29 ]; 3. the presence of chronic diseases and the development of side effects as discussed below; and 4. previous infections with SARS-CoV-2 and the development of strong side effects [ 30 , 31 ] after anti-SARS-CoV-2 vaccination. Further details about these comparisons are provided in the following paragraphs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although no parameters were associated with the magnitude of the side effects after the first dose of the BNT162b2 and ChAdOx1-S vaccines, being female, having chronic diseases, taking medicines routinely, and having a history of SARS-CoV-2 infection were associated with the magnitude of side effects after the second dose of the BNT162b2 vaccine, and having a history of allergy and being female were associated with the magnitude of side effects after the second dose of the ChAdOx1-S vaccine. Previous studies have reported the presence of associations between: 1. having a history of allergies and having an allergic reaction to the vaccine [ 26 ], local side effects [ 27 ], and non-allergic side effects [ 26 ]; 2. female sex and a higher magnitude of side effects [ 16 , 28 , 29 ]; 3. the presence of chronic diseases and the development of side effects as discussed below; and 4. previous infections with SARS-CoV-2 and the development of strong side effects [ 30 , 31 ] after anti-SARS-CoV-2 vaccination. Further details about these comparisons are provided in the following paragraphs.…”
Section: Discussionmentioning
confidence: 99%
“…It also suggests that such association is vaccine-dependent, which can result from the differences in the composition and mechanisms of the induced immune responses between the two vaccines [ 38 ]. Although previous studies have reported that the presence of a history of allergies was associated with the development of allergic reactions [ 26 ], the risk of developing local side effects [ 27 ], and the risk of developing non-allergic side effects [ 26 ] after anti-SARS-CoV-2 vaccination, to our knowledge, no other study has reported the presence of associations between having a history of allergies and developing strong side effects after these anti-SARS-CoV-2 vaccines. The precise reason for this association is not known, however it might result from a higher susceptibility of the immune system to components in the vaccine’s ingredients that can induce strong responses that do not involve the IgEs required for allergy [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most common side effects observed were pain/tenderness at the injection site and fever. The vaccine efficacy was estimated as 72.8% for WIV04 and 78.1% for HB02 against the symptomatic coronavirus disease 2019 and 79% against severe disease or hospitalization [ 10 , 11 , 12 ]. The Covilo vaccine has been evaluated in 39 clinical trials in 18 countries.…”
Section: Current Covid-19 Vaccine Platformsmentioning
confidence: 99%
“…The product contains sterile phosphate-buffered saline. It does not contain a preservative [ 10 , 11 , 12 ] (reactogenicity was seen within the first week after Sinopharm, Sputnik V, AZD1222, and COVIran Barekat vaccines: findings from the Iranian active vaccine surveillance system (published: 10 March 2023)).…”
Section: Current Covid-19 Vaccine Platformsmentioning
confidence: 99%
“…The rapid development of COVID-19 vaccination, the rapid progress in developing COVID-19 vaccines, combined with uncertainties about their safety, is a major factor contributing to the diminished trust in COVID-19 immunization efforts 2 , 8 . Although the majority of vaccination side effects are mild, a few rare and serious adverse events specific to each type of vaccine have been reported 3 , 9 . Therefore, post-vaccination surveillance is necessary to provide the necessary measures to deal with short, mid, and long-term complications 10 .…”
Section: Introductionmentioning
confidence: 99%